Pengaruh Kompetensi Aparatur Pengelola Dana Desa, Sistem Pengendalian Internal dan Transparansi Informasi terhadap Efektivitas Pengelolaan Dana Desa di Kecamatan Tugumulyo Kabupaten Musi Rawas - Silvy Afriayan Lestari; Kiagus Zainal Arifin; Rosy Armaini (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to determine the effect of the competence of the village fund management apparatus, internal control system and information transparency on the effectiveness of village fund management in Tugumulyo District, Musi Rawas Regency. The population in this study was seventeen villages in Tugumulyo sub-district. Using purposive sampling techniques, the sample of this study was 51 respondents. Data was collected by distributing questionnaires directly to respondents. The data analysis technique used is multiple linear regression with SPSS software version 25. The results showed that the competence of the village fund management apparatus, internal control system, and information transparency together have a positive effect on the efficiency of village fund management in Tugumulyo District, Musi Rawas Regency. Partially, the competence of the village fund management apparatus has a negative effect on the effectiveness of village fund management. The internal control system has a positive and significant effect on the effectiveness of village fund management. Information transparency has a positive and significant effect on the effectiveness of village fund management.